Bimetal composite nanomaterial and application thereof in glucose detection

By using tantalum-gold bimetallic composite nanomaterials synthesized by tantalum pentoxide and carbon quantum dots in glucose sensors, the problems of high enzyme cost and low sensitivity in the prior art are solved, and a low-cost and high-sensitivity glucose detection method is realized.

CN119794326APending Publication Date: 2025-04-11JIANGNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411844743.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing glucose sensors require expensive enzymes to be added and have problems of low sensitivity and unsatisfactory selectivity, and traditional gold nanomaterials are costly and time-consuming to prepare.

Method used

Tantalum pentoxide is used as a carrier, carbon quantum dots and tetrachloroauric acid are added to synthesize tantalum-gold bimetallic composite nanomaterials at high temperatures, and are used to electrochemically detect blood sugar concentration sensors.

Benefits of technology

A glucose detection method with lower cost, easier operation and more sensitive detection is realized, with a detection limit of 6.7×10-9M, a higher sensitivity, and no additional glucose oxidase is required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119794326A_ABST
    Figure CN119794326A_ABST
Patent Text Reader

Abstract

The invention discloses a bimetallic composite nanomaterial and application thereof in glucose detection, and belongs to the field of nanomaterials and electrochemical detection. Tantalum pentoxide is used as a carrier, carbon quantum dots are added, precious metal gold is doped to prepare the bimetallic nanomaterial Au / Ta-BGQD, and compared with a traditional gold nanomaterial, the bimetallic nanomaterial has higher selectivity and responsiveness to glucose. On the basis, when glucose is detected by using the bimetallic nano material as an electrochemical sensor, the characteristics of relatively high sensitivity and simplicity and convenience in operation are shown, the limit of detection (LOD) of the detection method disclosed by the invention reaches 6.7 * 10 <-9 > M, and the detection range is 2.0 * 10 <-8 > M-1. 0 * 10 <-6 > M.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a bimetallic composite nano material and application thereof in detecting glucose, belonging to the technical field of nano materials and electrochemical detection. Background Art

[0002] Glucose is an important source of energy for life activities. When blood sugar levels are abnormal and not regularly controlled, it can cause serious health complications and eventually lead to diabetes. Therefore, maintaining blood sugar levels within the appropriate range is crucial for diabetic patients to prevent complications such as heart attacks, blindness, kidney disease and amputations.

[0003] Several existing glucose sensors on the market usually require the help of enzymes (i.e. glucose oxidase, glucose dehydrogenase and hexokinase) to complete the detection, which are expensive and sensitive to environmental conditions (i.e. pH, temperature, humidity). In addition, traditional biosensors have the limitations of low sensitivity and unsatisfactory selectivity.

[0004] Electrochemical sensors have attracted much attention due to their rapidity, high sensitivity and low cost. In addition, nanocomposites have advantages such as high surface area, excellent catalytic ability, high sensitivity and selectivity. Based on these characteristics, it is expected that nanomaterials combined with electrochemistry can be used for human blood sugar testing to monitor glucose concentration.

[0005] Gold nanomaterials have great application prospects in non-enzymatic electrochemical glucose sensors due to their excellent high catalytic activity and fascinating biocompatibility. However, the application of precious metal materials is greatly limited by the high cost due to their own high price. Attempts to replace or partially replace gold with ordinary metals, but its sensing, catalytic and other properties are almost unaffected, is a great challenge for researchers to design electrochemical sensors.

[0006] The document “High electrochemical performance of glucose detection based on tapered gold nanostructures and MXene layers” uses glassy carbon electrodes and gold nanomaterials to prepare a method for enzyme-free detection of glucose content. However, this technology has the problems of long preparation time (more than 48 hours) and high cost (5mL5wt% Nafion solution) for raw material preparation.

[0007] Therefore, developing a glucose detection method with simple preparation, low cost and high sensitivity has extremely high practical and economic value. Summary of the invention

[0008] To solve the above problems, the present invention uses tantalum pentoxide as a carrier, adds quantum dots and tetrachloroauric acid, synthesizes a nano-scale material doped with tantalum and gold at high temperature, and uses this material in a sensor for electrochemical detection of blood sugar concentration. The present invention has the advantages of lower cost, simpler operation and more sensitive detection.

[0009] The first object of the present invention is to provide a method for preparing a tantalum-gold bimetallic composite nanomaterial, the method for preparing the bimetallic composite nanomaterial comprising:

[0010] (1) dissolving citric acid, arginine, serine and boric acid in water and heating for reaction; cooling, centrifuging, dialyzing and drying after the reaction to prepare carbon quantum dots;

[0011] (2) dissolving tantalate, carbon quantum dots and hydrogen peroxide in water, heating and stirring until clear and transparent; adding tetrachloroauric acid trihydrate, continuing heating and stirring to obtain a solid powder;

[0012] (3) annealing the solid powder and cooling it to obtain a tantalum-gold bimetallic composite nanomaterial.

[0013] In one embodiment, in step (1), the mass ratio of citric acid, arginine, serine and boric acid is 2-4: 2-3: 0.2-0.4: 0.10-0.20.

[0014] In one embodiment, in step (2), the usage ratio of tantalate, carbon quantum dots, hydrogen peroxide and tetrachloroauric acid trihydrate is 0.3-9 g: 0.03-1.2 g: 3-6 mL: 0.01-0.05 g.

[0015] In one embodiment, the heating reaction is carried out in an oven at 150-200° C. for 2-6 hours.

[0016] In one embodiment, the dialysis is (1000 Da) 5-15 hours.

[0017] In one embodiment, the annealing is performed at 750-900° C. for 2-5 hours.

[0018] In one embodiment, the preparation method of tantalate is:

[0019] 8-12 mL of deionized water and 3-8 mL of anhydrous ethanol were added to 2-6 mL of tantalum pentachloride n-butanol solution in sequence, and 1 M sodium hydroxide solution was added under rapid stirring to adjust the pH to 9. A large amount of white flocculent precipitate appeared at this time. The mother liquor was collected and centrifuged at 4200 rpm for 5-10 minutes to collect the precipitate, and the precipitate was repeatedly washed with deionized water and anhydrous ethanol until the pH was neutral to obtain tantalate.

[0020] The second object of the present invention is to provide a tantalum-gold bimetallic composite nanomaterial prepared by any of the above methods.

[0021] A third object of the present invention is to provide an electrochemical sensor for detecting glucose, wherein the preparation method of the electrochemical sensor comprises:

[0022] (1) Use polishing powder to polish the glassy carbon electrode, wash it and dry it;

[0023] (2) taking the above-mentioned tantalum-gold bimetallic composite nanomaterial and preparing it into a tantalum-gold bimetallic composite nanomaterial solution;

[0024] (3) Adding a tantalum-gold bimetallic composite nanomaterial solution to the center of a glassy carbon electrode and drying it; then adding a chitosan solution and drying it to obtain an electrochemical sensor.

[0025] In one embodiment, the gold bimetallic composite nanomaterial solution in step (2) is sonicated and vortexed until it is uniformly dispersed.

[0026] In one embodiment, the glassy carbon electrode has a diameter of 1 to 3 mm.

[0027] In one embodiment, the concentration of the tantalum-gold bimetallic composite nanomaterial solution in step (2) is 0.1-3 mg / mL; the concentration of the chitosan solution in step (3) is 5-15 mg / mL.

[0028] In one embodiment, the grinding time in step (1) is 3 to 10 minutes, and after grinding, anhydrous ethanol and deionized water are used for ultrasonic cleaning.

[0029] In one embodiment, in step (3), the amount of tantalum-gold bimetallic composite nanomaterial solution used is 1 to 8 μL, and the amount of chitosan used is 1 to 8 μL.

[0030] A fourth object of the present invention is to provide a use of any of the above electrochemical sensors in the preparation of glucose detection products;

[0031] Optionally, the detection product includes a detection probe, a detection kit, and a detection device.

[0032] A fifth object of the present invention is to provide a kit for detecting glucose, wherein the kit comprises any one of the above-mentioned electrochemical sensors.

[0033] A sixth object of the present invention is to provide a method for detecting glucose content, using any of the above electrochemical sensors or the kit according to claim 8, the detection method comprising:

[0034] Mix the buffer solution and the sample to be tested, immerse the electrochemical sensor in the solution to be tested, and detect the DPV peak current value; calculate the glucose content in the sample to be tested according to the standard curve;

[0035] The standard curve is: Ip(nA)=0.2482×[C glucose (M)]+154.87; where Ip (nA) is the peak current, nA; C glucose (M) is the glucose concentration, M;

[0036] Optionally, the volume ratio of the buffer to the sample to be tested is 1-2:1-2;

[0037] Optionally, the buffer solution and the sample to be tested are mixed and incubated at 28-32° C. for 20-40 minutes.

[0038] In one embodiment, the sample to be tested is a serum sample.

[0039] In one embodiment, the buffer is a sodium carbonate-bicarbonate buffer.

[0040] A seventh object of the present invention is to provide a method for improving the accuracy of glucose detection, using any of the above electrochemical sensors or the kit according to claim 8, the detection method comprising:

[0041] Mix the buffer solution and the sample to be tested, immerse the electrochemical sensor in the solution to be tested, and detect the DPV peak current value; calculate the glucose content in the sample to be tested according to the standard curve;

[0042] The standard curve is: Ip(nA)=0.2482×[C glucose (M)]+154.87; where Ip (nA) is the peak current, nA; C glucose (M) is the glucose concentration, M;

[0043] Optionally, the volume ratio of the buffer to the sample to be tested is 1-2:1-2;

[0044] Optionally, the buffer solution and the sample to be tested are mixed and incubated at 28-32° C. for 20-40 minutes.

[0045] Beneficial effects of the present invention

[0046] The present invention uses tantalum pentoxide as a carrier, adds carbon quantum dots and dopes with precious metal gold to prepare a bimetallic nanomaterial Au / Ta-BGQD. Compared with traditional gold nanomaterials, the material has higher selectivity and responsiveness to glucose. On this basis, the present invention uses the bimetallic nanomaterial as an electrochemical sensor to detect glucose, showing high sensitivity and easy operation.

[0047] Specifically, the present invention has the following advantages:

[0048] (1) Compared with the conventional gold nanomaterials used for glucose detection, the bimetallic nanomaterials used in the present invention contain less precious metal gold and have lower costs. In addition, the preparation method is simple, which reduces the time cost of raw material preparation.

[0049] (2) The detection limit (LOD) of the detection method of the present invention reaches 6.7×10 -9 M, detection range is 2.0×10 -8 M~1.0×10 -6 M, compared with conventional detection methods, has lower detection limit and higher sensitivity;

[0050] (3) The electrochemical sensor used in the present invention detects the glucose content in the blood without the need to add glucose oxidase or the like, and is simpler to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is the SEM image of the bimetallic nanomaterial;

[0052] Figure 2 CV curves of different modified electrodes; Figure 2 A in FIG. 1 is the CV curve of the bimetallic nanomaterial, that is, the CV curve of the bimetallic nanomaterial Ta / Au-BGQD glassy carbon electrode (GCE) in a 1 mM potassium ferrocyanide solution prepared in PBS at pH = 7; Figure 2 B in the figure is the CV curve of traditional gold nanomaterials, where b is the CV curve of Au-CQD-3 glassy carbon electrode (GCE) in 1 mM potassium ferrocyanide solution prepared in PBS at pH = 7; c is the CV curve of Au-CQD-2 glassy carbon electrode (GCE) in 1 mM potassium ferrocyanide solution prepared in PBS at pH = 7; d is the CV curve of Au-CQD-1 glassy carbon electrode (GCE) in 1 mM potassium ferrocyanide solution prepared in PBS at pH = 7.

[0053] Figure 3 Electrochemical impedance spectroscopy (EIS) graphs of different modified electrodes; Figure 3 In the figure, a is the impedance (EIS) of Ta / Au-BGQD at glassy carbon electrode in 1 mM potassium ferrocyanide solution prepared in PBS at pH = 7; b is the EIS curve of Au-CQD-1 glassy carbon electrode (GCE) in 1 mM potassium ferrocyanide solution prepared in PBS at pH = 7; c is the EIS curve of Au-CQD-2 glassy carbon electrode (GCE) in 1 mM potassium ferrocyanide solution prepared in PBS at pH = 7; d is the EIS curve of Au-CQD-3 glassy carbon electrode (GCE) in 1 mM potassium ferrocyanide solution prepared in PBS at pH = 7.

[0054] Figure 4 Different scan rate-current density linear diagrams of different modified electrodes; Figure 4 a in A is the current density linear diagram of Ta / Au-BGQD on glassy carbon electrode in 1M sodium chloride solution; Figure 4 In B, b is the current density linear graph of Au-CQD-2 at glassy carbon electrode (GCE) in 1M sodium chloride solution; c is the current density linear graph of Au-CQD-3 at glassy carbon electrode (GCE) in 1M sodium chloride solution; d is the current density linear graph of Au-CQD-1 at glassy carbon electrode (GCE) in 1M sodium chloride solution.

[0055] Figure 5 The differential pulse voltammetry (DPV) curve and linear diagram of the electrochemical detection of glucose by the bimetallic nanomaterial Ta / Au-BGQD are shown in Figure 1. Figure 5 A shows the DPV curves of different glucose concentrations; Figure 5 B shows the Ip value and glucose level logarithmic curve. DETAILED DESCRIPTION

[0056] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0057] Test method:

[0058] Electrochemical detection steps:

[0059] 5 μL of bimetallic nanomaterial stock solution and 5 μL of chitosan solution were dripped into the center of the glassy carbon electrode, and the working electrode was placed in a 40°C oven for drying. Carbonic acid-sodium bicarbonate buffer solution with pH=7.4 was used as the solvent, and test solutions with different concentrations of glucose were prepared. The DPV curve was measured in the three-electrode system to obtain the peak current.

[0060] The peak current was brought into the standard curve Ip (nA) = 0.2482 × [Cglucose (M)] + 154.87 to calculate the glucose concentration. Raw materials used in the examples:

[0061] Citric acid monohydrate (hereinafter referred to as citric acid), L-arginine (hereinafter referred to as arginine), L-serine (hereinafter referred to as serine), boric acid, tantalum pentachloride n-butanol solution (hereinafter referred to as tantalate), 30% hydrogen peroxide, anhydrous ethanol, pH 7.4 carbonic acid-sodium bicarbonate buffer solution, tetrachloroauric acid trihydrate, disodium hydrogen phosphate, sodium dihydrogen phosphate, potassium chloride, glucose, sodium chloride, potassium ferrocyanide, potassium ferrocyanide, sodium hydroxide and other reagents were purchased from Sinopharm Group.

[0062] Example 1: Preparation of bimetallic nanomaterials

[0063] The preparation method of bimetallic nanomaterials comprises the following steps:

[0064] (1) 3.000 g of citric acid, 2.486 g of arginine, 0.3 g of serine and 0.175 g of boric acid were mixed evenly, added into 5 mL of deionized water and stirred thoroughly, transferred into a 10 mL polytetrafluoroethylene autoclave and reacted in an oven at 160 ° C for 4 h; after cooling to room temperature, centrifuged at 8000 rpm for 5 min to remove impurities, the supernatant was collected and dialyzed (1000 Da) for 12 hours, the solvent was removed and further freeze-dried to obtain a reddish brown powder, i.e., carbon quantum dots, which was stored in a refrigerator at 4 ° C;

[0065] (2) 0.6 g of tantalate, 6 mL of 100 mg / mL carbon quantum dot aqueous solution and 5 mL of 30% hydrogen peroxide were added to 10 mL of deionized water in sequence, and the mixture was stirred continuously in a 60° C. constant temperature water bath until the solution became clear and transparent, 30 mg of tetrachloroauric acid trihydrate was added, and stirring was continued until the water was completely evaporated to obtain a solid;

[0066] (3) The solid was placed in a square crucible, transferred to a tube furnace, annealed at 850 °C for 3 h, and cooled to room temperature to obtain a bimetallic nanomaterial, named Ta / Au-BGQD, which was mixed with water to form a 1 mg / mL stock solution and stored in a refrigerator at 4 °C.

[0067] The morphology of bimetallic nanomaterials was observed using SEM electron microscopy. Figure 1 As shown in the SEM image, the bimetallic nanomaterial has a rounded square shape and uniform particle size. The micro / nanostructure achieves high electronic conductivity and large specific surface area.

[0068] Comparative Example 1: Traditional gold nanomaterials with different precious metal contents

[0069] The specific method for preparing traditional gold nanomaterials is as follows:

[0070] Heat 1.27 mL of 10 mM tetrachloroauric acid trihydrate in a 95°C constant temperature water bath for 5 min, then add 10 mL of 5 mg / mL

[0071] The carbon quantum dot aqueous solution prepared in Example 1 was reacted at 95°C for 8 minutes until the solution changed from light yellow to light brown. After cooling to room temperature, the mother liquor was centrifuged at 8000 rpm for 10 minutes, the upper liquid was removed, and the precipitated solid was retained. The solid was washed with deionized water 3 times, and finally the solid was concentrated in 1 mL of ultrapure water (concentration of 0.11 g / mL) and stored in a refrigerator at 4°C.

[0072] 8.7 μL, 91.3 μL, and 100.0 μL of the above-mentioned traditional gold nanomaterial concentrate were taken respectively to prepare 1 mL of control material, which were recorded as Au-CQD-1, Au-CQD-2, and Au-CQD-3 respectively. The content of precious metal gold in the control group materials increased successively, and their CV curves and electrochemical impedance were tested by the same method.

[0073] Example 2: Preparation of electrochemical sensor

[0074] The preparation method of the electrochemical sensor comprises the following steps:

[0075] (1) A glassy carbon electrode with a diameter of Φ = 2 mm was polished with aluminum oxide polishing powder for 5 min, ultrasonicated with anhydrous ethanol and deionized water for 5 min, and dried in an oven at 40 °C;

[0076] (2) The stock solutions prepared in Example 1 and Comparative Example 1 (i.e., Ta / Au-BGQD, Au-CQD-1, Au-CQD-2, and Au-CQD-3) were ultrasonicated for 10 min and vortexed for 3 min;

[0077] (3) 5 μL of bimetallic nanomaterial stock solution was added to the center of the glassy carbon electrode and dried in a 40°C oven. Then 5 μL of 10 mg / mL chitosan solution was added and dried in a 40°C oven to obtain electrochemical sensors, namely Ta / Au-BGQD, Au-CQD-1 glassy carbon electrode, Au-CQD-2 glassy carbon electrode, and Au-CQD-3 glassy carbon electrode.

[0078] Example 3: Preparation of electrochemical sensor and feasibility of glucose detection

[0079] The electrochemical sensor prepared in Example 2 was used to test its feasibility of glucose detection.

[0080] The results of CV curve and EIS curve are as follows Figure 2 , Figure 3 shown. Figure 2 It shows that there is a pair of redox peaks in all CV curves, which verifies that Fe(CN)6 4- Redox can be performed on all electrode surfaces; judging from the difference in CV curves, the bimetallic nanomaterial Ta / Au-BGQD has a redox ability much higher than that of traditional gold nanomaterials Au-BGQD-1, Au-BGQD-2, and Au-BGQD-3.

[0081] Figure 3 The results show that the ion diffusion rate of the bimetallic nanomaterial Ta / Au-BGQD is much higher than that of the traditional gold nanomaterials Au-BGQD-1, Au-BGQD-2, and Au-BGQD-3, and their ion diffusion coefficients are 1.72×10-12 cm 2 / s, 2.37×10 -15 cm 2 / s, 4.05×10- 15 cm 2 / s、7.11×10 -15 cm 2 / s, indicating that the bimetallic nanomaterials have a higher ion diffusion rate and can help the electrochemical sensor respond faster.

[0082] Figure 4 The linear graphs of the current density of the bimetallic nanomaterials Ta / Au-BGQD and the traditional gold nanomaterials Au-BGQD-1, Au-BGQD-2, and Au-BGQD-3 at different scan rates. The slope of the curve is the double layer current C DL , the electrochemical activity of the material can be obtained through the double-layer current, and then its sensing ability in detecting glucose can be evaluated;

[0083] Among them, the bimetallic nanomaterial Ta / Au-BGQD has a higher electrochemical activity, and the curve is: y=0.503x+14.043, R 2 =0.9927;

[0084] Among traditional gold nanomaterials, the electrochemical activity curve of Au-BGQD-1 is: y=0.016x+0.8773, R 2 =0.9909;

[0085] The electrochemical activity curve of Au-BGQD-2 is: y=0.0166x+2.0209, R 2 =0.987;

[0086] The electrochemical activity curve of Au-BGQD-3 is: y = 0.0216x + 1.0631R 2 =0.9846.

[0087] Figure 5 The differential pulse voltammetry (DPV) curve and linear diagram of the electrochemical detection of glucose by the bimetallic nanomaterial Ta / Au-BGQD are shown in Figure 1. Figure 5 A shows the DPV curves of glucose solutions with different concentrations of 20 nM, 40 nM, 60 nM, 80 nM, 100 nM, 120 nM, 140 nM, 160 nM, 180 nM, 200 nM, 400 nM, 600 nM, 800 nM and 1000 nM; Figure 5 B represents the linear curve of Ip value and glucose concentration, y = 0.2482x + 154.87, R 2 =0.9963, LOD = 6.7 × 10 -9M. The results show that the bimetallic nanomaterial Ta / Au-BGQD electrochemical sensor has a high responsiveness to glucose, a low detection line and a high degree of fit, that is, it can be used to detect glucose.

[0088] Example 4: Application of electrochemical sensor in glucose detection

[0089] 1. Standard curve of glucose concentration corresponding to current peak and detection limit determination

[0090] The bimetallic nanomaterial Ta / Au-BGQD electrochemical sensor prepared in Example 3 was used to prepare a glucose content detection standard curve, and the steps were as follows:

[0091] (1) preparing 20 nM, 40 nM, 60 nM, 80 nM, 100 nM, 120 nM, 140 nM, 160 nM, 180 nM, 200 nM, 400 nM, 600 nM, 800 nM and 1000 nM glucose aqueous solutions;

[0092] (2) 5 mL of the test solution with different glucose concentrations was mixed with 5 mL of pH 7.4 carbonate-sodium bicarbonate buffer solution in equal volumes, and the DPV curve was measured in a three-electrode electrochemical system to obtain the peak current. The linear relationship between the current peak value (Ip value) and the glucose concentration was calculated.

[0093] The results are as follows Figure 5 As shown in B, the results show that Ip increases with the increase of glucose concentration, and there is a relationship curve between Ip value and glucose concentration. -8 M~1×10 -6 M, Ip(nA) increases linearly with the increase of glucose concentration, and its linear regression equation is Ip(nA)=0.2482×[C glucose (M)]+154.87, correlation coefficient (R 2 ) was 0.9963, and the detection limit (LOD) reached 6.7×10 -9 M(S / N=3).

[0094] 2. Electrochemical detection of glucose

[0095] A method for electrochemically detecting glucose, comprising the following steps:

[0096] (1) Add 5 μL of bimetallic nanomaterial stock solution to the center of the glassy carbon electrode and dry it in a 40°C oven. Then add 5 μL of chitosan solution and dry it in a 40°C oven.

[0097] (2) The sample to be tested was mixed with an equal volume of a carbonic acid-sodium bicarbonate buffer solution with a pH value of 7.4 (volume ratio 1:1, 5 mL each), and its DPV peak current was measured.

[0098] (3) Substitute the peak current into the calibration curve Ip(nA) = 0.2482×[C glucose (M)] + 0.9963, and the glucose concentration in the sample was calculated.

[0099] 3. Comparison of different glucose detection methods

[0100] The results of comparing “2. Electrochemical detection of glucose” with common methods of glucose detection are shown in Table 1.

[0101] Table 1 Different glucose detection methods

[0102]

[0103] Table 1 is a comparison of the linear range and detection limit of the present method with the published methods. It can be seen that compared with the published glucose detection method, the glucose detection method of the present invention has a lower detection limit and is more sensitive.

[0104] Example 5: A glucose detection kit

[0105] A glucose detection kit comprises the electrochemical sensor prepared in Example 3 and a carbonic acid-sodium bicarbonate buffer solution.

[0106] The detection method of the kit is:

[0107] (1) Mix the buffer solution and the sample to be tested in a 1:1 volume ratio and keep at 30°C for 30 min.

[0108] (2) Immerse the electrochemical sensor in the test solution, test its DPV peak current value, and plot the glucose concentration versus DPV peak current value curve: Ip (nA) = 0.2482 × [C glucose (M)]+154.87.

[0109] (3) Substitute the detected peak current into the calibration curve Ip (nA) = 0.2482 × [C glucose (M)] + 154.87, the glucose concentration in the sample to be tested was calculated.

[0110] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a tantalum-gold bimetallic composite nanomaterial, characterized in that: The preparation method of the bimetallic composite nanomaterial comprises: (1) dissolving citric acid, arginine, serine and boric acid in water and heating for reaction; cooling, centrifuging, dialyzing and drying after the reaction to prepare carbon quantum dots; (2) dissolving tantalate, carbon quantum dots and hydrogen peroxide in water, heating and stirring until clear and transparent; adding tetrachloroauric acid trihydrate, continuing heating and stirring to obtain a solid powder; (3) annealing the solid powder and cooling it to obtain a tantalum-gold bimetallic composite nanomaterial.

2. The method according to claim 1, characterized in that In step (1), the mass ratio of citric acid, arginine, serine and boric acid is 2-4:2-3:0.2-0.4:0.10-0.

20.

3. The method according to claim 1, characterized in that In step (2), the dosage ratio of tantalate, carbon quantum dots, hydrogen peroxide and tetrachloroauric acid trihydrate is 0.3-9 g: 0.03-1.2 g: 3-6 mL: 0.01-0.05 g.

4. Tantalum-gold bimetallic composite nanomaterial prepared by the method described in any one of claims 1 to 3.

5. An electrochemical sensor for detecting glucose, characterized in that: The electrochemical sensor preparation method comprises: (1) Use polishing powder to polish the glassy carbon electrode, wash it and dry it; (2) taking the tantalum-gold bimetallic composite nanomaterial as described in claim 4 and preparing it into a tantalum-gold bimetallic composite nanomaterial solution; (3) Adding a tantalum-gold bimetallic composite nanomaterial solution to the center of a glassy carbon electrode and drying it; then adding a chitosan solution and drying it to obtain an electrochemical sensor.

6. The electrochemical sensor according to claim 5, characterized in that The concentration of the tantalum-gold bimetallic composite nanomaterial solution in step (2) is 0.1 to 3 mg / mL; the concentration of the chitosan solution in step (3) is 5 to 15 mg / mL.

7. Use of the electrochemical sensor according to any one of claims 5 to 6 in the preparation of glucose detection products; Optionally, the detection product includes a detection probe, a detection kit, and a detection device.

8. A kit for detecting glucose, characterized in that: The kit comprises the electrochemical sensor according to any one of claims 5 to 6.

9. A method for detecting glucose content, characterized in that: Using the electrochemical sensor according to any one of claims 5 to 6 or the kit according to claim 8, the detection method comprises: Mix the buffer solution and the sample to be tested, immerse the electrochemical sensor in the solution to be tested, and detect the DPV peak current value; calculate the glucose content in the sample to be tested according to the standard curve; The standard curve is: Ip(nA)=0.2482×[C glucose (M)]+154.87; where Ip (nA) is the peak current, nA; C glucose (M) is the glucose concentration, M; Optionally, the volume ratio of the buffer to the sample to be tested is 1-2:1-2; Optionally, the buffer solution and the sample to be tested are mixed and incubated at 28-32° C. for 20-40 minutes.

10. A method for improving glucose detection accuracy, characterized in that: Using the electrochemical sensor according to any one of claims 5 to 6 or the kit according to claim 8, the detection method comprises: Mix the buffer solution and the sample to be tested, immerse the electrochemical sensor in the solution to be tested, and detect the DPV peak current value; calculate the glucose content in the sample to be tested according to the standard curve; The standard curve is: Ip(nA)=0.2482×[C glucose (M)]+154.87; where Ip (nA) is the peak current, nA; C glucose (M) is the glucose concentration, M; Optionally, the volume ratio of the buffer to the sample to be tested is 1-2:1-2; Optionally, the buffer solution and the sample to be tested are mixed and kept at 28-32° C. for 20-40 minutes before testing.